THE LEGAL STATUS OF RUSSIAN IMMIGRANTS IN THE USA DURING THE POST-WAR PERIOD - Golovkin, Aleksandr A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
The article deals with the legal status of the Russian emigrants in the USA in the post-war period. There are considered the peculiarities of the new immigration and refugee law, its features and inﬂuence on the new Russian emigration wave to America. The author analyzes «Truman Directive», the Law about displaced persons («DP») of 1948 and the amendments to the Law. The directive envisaged special immigration quotas for DP (more than 11 million in the post-war Europe). The number of migrants to the USA extremely increased after the enactment of the Refugee Law. The author shows the key role of the Refugee factor in the US policy during the Cold War and in the USSR - USA bilateral relations in particular. The article presents the scheme of collaboration between special Refugee organizations (United Nations Relief and Rehabilitation Administration and Committee of International Relief Association ) to provide selection, transfer and adaptation of DP in the US. The author provides examples from the reports of public, charity and religious organizations on the successful adaptation of Russian emigrants. There is shown how these organizations helped Russian emigrants in resettlement, job hunting, adaptation and socialization. It was the ﬁrst time in the American history, when the migration law had exercised these functions.The principal issues of the post-war wave of the Russian emigration were the ones of recognition of their refugee status, obtaining residency as well as citizenship. Legal assistance in this issue, as well as in the study of the language and cultural adaptation was provided by emigration charity organizations. An important role in the ﬁeld of information support of immigrants was played by the Russian-language press. The article is based on some statistics and sources from Bakhmeteff Archive at Columbia University, as well as emigrant newspapers “The Modern Time”, “New Russian Word”, “Russia” of 1949-1970.